Soil EC index – based prediction of rice growing and yield in the Mekong Delta - Ho, The Anh; Nguyen, Van Khanh; Bui, Van Huu; Nguyen, Chi Ngon (Asian Journal of Agriculture and Rural Development, 2025)
This research explores the use of soil electrical conductivity (EC) in rice cultivation, focusing on soil EC correlation with vegetation indices (NDVI, NDRE) and soil EC impact on yield. A total of 228 soil EC, NDVI, and NDRE data points were collected from an 11,000 m² field in Hau Giang and Can Tho City. Soil EC was measured at the beginning of the season, and at 39 and 49 days after sowing. NDVI was recorded on days 39, 49, 60, and 72, with initial values set to zero due to no crop presence. Results show that soil EC decreased from the start to day 49, while NDVI and NDRE increased. Spearman correlation analysis revealed strong relationships between early soil EC and NDVI at days 39 and 49 (r = 0.82, 0.71), and between soil EC at day 49 (EC 49) and NDRE at later stages (r = 0.594, 0.565). Additionally, 150 soil EC and yield samples from five Mekong Delta regions were used in an LSTM model (70% training, 30% testing), achieving high accuracy (RMSE = 0.0919, MAE = 0.0634, R2 = 0.8492). The findings suggest that soil EC is a valuable indicator for monitoring crop growth and managing rice production, particularly in areas affected by salinity due to climate change.